Persepsi Siswa Terhadap Penerapan Model Pembelajaran Discovery Learning - Melinda Riani Rahim; Rusiyah Rusiyah; Masruroh Masruroh (Universitas Negeri Gorontalo, 2026)
This study aims to analyze students' perceptions of the implementation of the Discovery Learning model using a Likert scale. A quantitative descriptive method was employed with a questionnaire instrument consisting of 15 items administered to 29 students of class XC IPS at SMA Negeri 1 Suwawa for the academic year 2025/2026. The results showed an average student response percentage of 89.06%, classified as